Establishing Nanoscale Circuitry by Designing a Structure with Atomic Short‐range Order for High‐Rate Energy Storage - Yang, Liting; Liang, Guisheng; Liu, Minmin; Du, Yiqian; Xiong, Xuhui; Chen, Guanyu; Che, Renchao (Advanced materials (Weinheim), 2025)
High‐rate materials necessitate the rapid transportation of both electrons and ions, a requirement that becomes especially challenging at practical mass loadings (>10 mg cm2). To address this challenge, a material is designed with an architecture having atomic‐scale short‐range order. This design establishes internal nanoscale circuitry at the particle level, which facilitates rapid electronic and ionic transport within micrometer‐sized niobium tungsten oxides. The architecture features alternating cerium‐depleted and cerium‐enriched regions. The continuous cerium‐enriched regions with enhanced conductivity provide multilane highways for electron mobility by functioning as electron‐conducting wires that significantly boost the overall conductivity. The cerium‐depleted regions effectively mitigate electrostatic repulsion and promote rapid ion transport through ion‐conducting channels. These structural characteristics provide a continuous network that supports both electrical migration and chemical diffusion to amplify the areal capacity and rate capability even at high mass loadings. These findings not only expand the fundamental understanding of the design of optimal host lattices for advanced energy storage systems but also of the practical application of microsized high‐rate electrode materials. A microsized perovskite oxide Ce0.266W0.1Nb0.9O3 is engineered as an anode material for high‐rate, long‐life Li+ storage, demonstrating impressive performance by maintaining both high areal capacity and high rate capability, even at high mass loadings. This outstanding electrochemical behavior is primarily attributed to the nanoscale circuitry formed by an atomic‐scale short‐range order structure.